PERAN CINTA MEREK MEMEDIASI PENGARUH PENGALAMAN MEREK TERHADAP LOYALITAS MEREK - Milinia, Ni Made Ari Mas; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p12, 2023)
Brand loyalty is related to the level of customer tendency to make repeat purchases by satisfied customers and positively evaluate the product, to gain loyalty it is necessary to make customers have a good experience and brand love for the I Look Daily brand. This study aims to examine the effect of brand experience on brand loyalty, brand experience on brand love, brand love on brand loyalty, and brand love in mediating the effect of brand experience on brand loyalty. This research was conducted in Denpasar City, the number of samples used was 130 respondents with purposive sampling method. Sample collection was done online via google form with a questionnaire instrument using a Likert scale. The collected data is then analyzed using path analysis techniques. The results of this study indicate that brand experience has a significant and positive effect on brand love, brand experience has a significant and positive effect on brand loyalty, brand love has a significant and positive effect on brand loyalty, and there is an influence of brand love in partially mediating the effect of brand experience on brand loyalty.